Papers (The Association BridgetownBB, 2001)
Focuses on the impact on and challeges of globalization to public sector unions in the Caribbean. Sees the public services as the key to economic development. Presents a plan for W.I. cricket. Looks at the Caricom Single Market and Economy and highlights the Caribbean Court of Justice. Discusses the IDB loans and health sector reform.
Keywords: TRADE UNIONS